2000
DOI: 10.1136/adc.83.2.128
|View full text |Cite
|
Sign up to set email alerts
|

Re-vaccination of 421 children with a past history of an adverse vaccine reaction in a special immunisation service

Abstract: Background-In Australia an adverse event following immunisation (AEFI), with the exception of anaphylaxis and encephalopathy, is no longer considered an absolute contraindication to continuing vaccination with the suspect vaccine. Despite these recommendations there is a paucity of information on the revaccination of such children. Aims-To describe the re-vaccination of a large number of children with a past history of an AEFI. Methods-A review of children attending special immunisation services in three Austr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(34 citation statements)
references
References 12 publications
0
32
0
2
Order By: Relevance
“…This information should be shared with parents and patients, since they are often worried that VAE might reappear after subsequent vaccination events. Indeed, this is the most common reason leading to revaccination refusal [9] and noncompletion of vaccination schedules [28].…”
Section: Discussionmentioning
confidence: 99%
“…This information should be shared with parents and patients, since they are often worried that VAE might reappear after subsequent vaccination events. Indeed, this is the most common reason leading to revaccination refusal [9] and noncompletion of vaccination schedules [28].…”
Section: Discussionmentioning
confidence: 99%
“…Gold et al [20], after studying 970 children revaccinated with booster doses, concluded that only anaphylaxis and encephalopathy are absolute contraindications for continuing the vaccination programme. Katoulis et al [4] suggested that EM minor is a mild adverse reaction, and their studied patient completed the vaccination programme successfully.…”
Section: Discussionmentioning
confidence: 99%
“…In one study of 970 children revaccinated with booster doses, 469 experienced an adverse reaction, of whom 176 experienced a significant neurological or allergic reaction. The majority (421/469) of these children were revaccinated, and only 1 child developed a significant neurological event, which was transient and resolved spontaneously [16]. An adverse reaction following immunization, with the exception of anaphylaxis and encephalopathy, is no longer considered an absolute contraindication for continuing vaccination with the suspect vaccine [3].…”
Section: Discussionmentioning
confidence: 99%